Catalysis-Induced Highly-Stable Interface on Porous Silicon for High-Rate Lithium-Ion Batteries - Han, Zhuobin; Maitarad, Phornphimon; Yodsin, Nuttapon; Zhao, Baogang; Ma, Haoyu; Liu, Kexin; Hu, Yongfeng; Jungsuttiwong, Siriporn; Wang, Yumei; Lu, Li; Shi, Liyi; Yuan, Shuai; et al. (Nano-Micro Letters, 2025)
Silicon stands as a key anode material in lithium-ion battery ascribing to its high energy density. Nevertheless, the poor rate performance and limited cycling life remain unresolved through conventional approaches that involve carbon composites or nanostructures, primarily due to the un-controllable effects arising from the substantial formation of a solid electrolyte interphase (SEI) during the cycling. Here, an ultra-thin and homogeneous Ti doping alumina oxide catalytic interface is meticulously applied on the porous Si through a synergistic etching and hydrolysis process. This defect-rich oxide interface promotes a selective adsorption of fluoroethylene carbonate, leading to a catalytic reaction that can be aptly described as “molecular concentration-in situ conversion”. The resultant inorganic-rich SEI layer is electrochemical stable and favors ion-transport, particularly at high-rate cycling and high temperature. The robustly shielded porous Si, with a large surface area, achieves a high initial Coulombic efficiency of 84.7% and delivers exceptional high-rate performance at 25 A g−1 (692 mAh g−1) and a high Coulombic efficiency of 99.7% over 1000 cycles. The robust SEI constructed through a precious catalytic layer promises significant advantages for the fast development of silicon-based anode in fast-charging batteries. Highlights: 1 In situ etching and co-growth of ultra thin defect-rich oxide layers on porous silicon. 2 Through the construction of nano-sized catalytic interface, the electrolyte addition FEC would decompose to a LiF-rich solid electrolyte interphase (SEI). 3 The robust SEI on porous structured silicon performs high-rate stability at varied temperatures.